A Marxian-Senian critique of Zambia's political economy of labour: Chinese-State capital in Zambia's copper mining industry - Sobahle, Busiswa (Stellenbosch : Stellenbosch University, 2021., 2021)
Thesis (MA)--Stellenbosch University, 2021.